LA RELACION ENTRE LA FORMACION PROFESIONAL DE LOS EGRESADOS DE LA FACULTAD DE CIENCAS DE LA EDUCACION DE LA UNIVERSIDAD TECNICA DE BABAHOYO Y SU INFLUENCIA CON EL DESARROLLO SOCIO-ECONOMICO DEL CANTON BABAHOYO - IVAN ROMERO GUERRA (2003)
THE RELATIONSHIP BETWEEN THE PROFESSIONAL TRAINING OF GRADUATES FROM THE FACULTY OF EDUCATIONAL SCIENCES OF THE TECHNICAL UNIVERSITY OF BABAHOYO AND ITS INFLUENCE WITH THE SOCIO-ECONOMIC DEVELOPMENT OF THE BABAHOYO CANTON